Duration of Respiratory Failure After Trauma Is Not Associated With Increased Long-Term Mortality. Issue 8 (August 2018) - Cook, Mackenzie R.; O'Connell, Kathleen; Qiu, Qian; Riggle, Andrew J.; Shoultz, Thomas H.; Maine, Rebecca G.; Arbabi, Saman; O'Keefe, Grant E.; Cuschieri, Joseph; Maier, Ronald V.; Robinson, Bryce R. H.
Abstract : Objectives: Although 1-year survival in medically critically ill patients with prolonged mechanical ventilation is less than 50%, the relationship between respiratory failure after trauma and 1-year mortality is unknown. We hypothesize that respiratory failure duration in trauma patients is associated with decreased 1-year survival. Design: Retrospective cohort of trauma patients. Setting: Single center, level 1 trauma center. Patients: Trauma patients admitted from 2011 to 2014; respiratory failure is defined as mechanical ventilation greater than or equal to 48 hours, excluded head Abbreviated Injury Score greater than or equal to 4. Interventions: None. Measurements and Main Results: Mortality was calculated from the Washington state death registry. Cohort was divided into short (⩽ 14 d) and long (> 14 d) ventilation groups. We compared survival with a Cox proportional hazard model and generated a receiver operator characteristic to describe the respiratory failure and mortality relationship. Data are presented as medians with interquartile ranges and hazard ratios with 95% CIs. We identified 1, 503 patients with respiratory failure; median age was 51 years (33–65 yr) and Injury Severity Score was 19 (11–29). Median respiratory failure duration was 3 days (2–6 d) with 10% of patients in the long respiratory failure group. Cohort mortality at 1 year was 16%, and there was no difference in mortality between short and long duration of respiratory failure. Predictions for 1-year mortality based on respiratory failure duration demonstrated an area under the receiver operator characteristic curve of 0.57. We determined that respiratory failure patients greater than or equal to 75 years had an increased hazard of death at 1 year, hazard ratio, 6.7 (4.9–9.1), but that within age cohorts, respiratory failure duration did not influence 1-year mortality. Conclusions: Duration of mechanical ventilation in the critically injured is not associated with 1-year mortality. Duration of ventilation following injury should not be used to predict long-term survival. Abstract : Supplemental Digital Content is available in the text.